2020
DOI: 10.3390/ijerph17249491
|View full text |Cite
|
Sign up to set email alerts
|

Cut-Off Values in the Prediction of Success in Olympic Distance Triathlon

Abstract: Cut-off points and performance-related tools are needed for the development of the Olympic distance triathlon. The purposes of the present study were (i) to determine cut-off values to reach the top three positions in an Olympic distance triathlon; (ii) to identify which discipline present the highest influence on overall race performance and if it has changed over the decades. Data from 1989 to 2019 (n = 52,027) from all who have competed in an official Olympic distance triathlon events (World Triathlon Serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…The present analyses did not find any significant effect of sex over the contribution of each discipline (%) to overall performance in all four triathlon distances. The literature is consistently showing that males are faster than females across all triathlon distances ( Lepers, 2019 ; Gadelha et al, 2020 ), and in all three triathlon disciplines ( Lepers et al, 2013 ; Lepers, 2019 ). Nevertheless, our results show that performance difference does not change the relative contribution and importance of each discipline to overall performance.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The present analyses did not find any significant effect of sex over the contribution of each discipline (%) to overall performance in all four triathlon distances. The literature is consistently showing that males are faster than females across all triathlon distances ( Lepers, 2019 ; Gadelha et al, 2020 ), and in all three triathlon disciplines ( Lepers et al, 2013 ; Lepers, 2019 ). Nevertheless, our results show that performance difference does not change the relative contribution and importance of each discipline to overall performance.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, shorter triathlon distances (e.g., Sprint- and Olympic-distance triathlon) have legal drafting in the cycling portion, which can significantly change a race dynamic. For example, faster swimmers can start cycling in a leading peloton, which causes some athletes to swim faster than planned in order to closely follow a fast pack of athletes ( Gadelha et al, 2020 ). Different triathlon distances show a difference in race dynamics, and the contribution of each discipline varies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding sex differences, some authors suggest that future studies are required to clarify why the sex difference in running is greater compared to swimming and cycling in international short distance triathlon races with drafting [10]. In the current literature, some authors point out that men were shown to be faster triathletes than women [12], while other analyses did not find any significant effect of sex on the contribution of each discipline (%) to overall performance in all four triathlon distances [14]. Barbosa et al [29] suggested that cycling was the discipline with the highest influence on overall race time for both sexes in long-distance events.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the physiological training objectives for athletes are different for the Olympic distance [4] and the sprint distance [3,5]. The study of the contribution of segments and transitions to the overall results of the competition has been widely focused on the Olympic distance [6][7][8][9][10][11][12]. However, very little data are available on sprint distance triathlon performance, especially 2 of 11 for high-level international races [13], despite the fact that, depending on the distance of the triathlon, the discipline for predicting overall triathlon performance changes [14].…”
Section: Introductionmentioning
confidence: 99%